New jatropholane-type diterpenes from Jatropha curcas cv. Multiflorum CY Yang - Yang, Yuan-Feng (Springer Berlin Heidelberg, 2013)
Three new jatropholane-type diterpenoids, jatropholones C-E (1–3), along with seven other known compounds, including sikkimenoid B (4), jatrophaldehyde (5), epi-jatrophaldehyde (6), epi-jatrophol (7), jatrophol (8), jatropholone A (9), and jatropholone B (10), were isolated from the roots of a natural cultivar of Jatropha curcas (J. curcas cv. Multiflorum CY Yang). The structural elucidations of 1–3 were accomplished by extensive NMR analysis. Compounds 4, 6, and 8 demonstrated inhibition activity against the microorganisms with the MIC values from 0.10 to 0.18 mg/mL. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-013-0031-x and is accessible for authorized users.